Determinants of Profitability in Islamic Commercial Banks - Shelvita Meilani Kusuma Wati; Imron Rosyadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the elements that affect profitability in Islamic Commercial Banks (BUS) in Indonesia from 2019 to 2023. It specifically analyzes the influence of the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and MSME Financing on Return on Assets (ROA). Utilizing secondary time-series data from 12 banks overseen by the Financial Services Authority (OJK), a quantitative descriptive methodology is applied. The relationships among these variables are evaluated through multiple linear regression and classical assumption testing. The findings reveal that CAR significantly and positively affects ROA, indicating that higher capital reserves improve financial stability and support operational activities. Conversely, NPF does not significantly affect ROA, implying that although it introduces certain risks, it does not directly hinder profitability. Additionally, MSME financing does not exhibit a significant effect on ROA, as delayed repayments may hinder profit management.